Kesadaran Hukum Masyarakat Dalam Pemanfaatan Lahan Pekarangan Di Kelurahan Oepura Kecamatan Maulafa Ditinjau Dari Peraturan Daerah Kota Kupang Nomor 7 Tahun 2000 Tentang Ruang Terbuka Hijau - Benu, Seprianus Aleksander; Monteiro, Yosef M; Radji, Megi O (Artemis Law Journal, 2025)
Green open space (RTH) is part of the open spaces of an urban area filled with plants, vegetation, and vegetation to support the direct and indirect benefits generated by RTH in the city, namely security, comfort, welfare, and beauty of the urban area. The availability of green open space in Kupang City is categorized as sufficient. The Kupang City Government (Pemkot) issued Kupang City Regional Regulation Number 7 of 2000 concerning RTH and circulars for offices, private business actors and the general public, to provide land designated as parks or mini gardens in their respective yard areas. This study discusses (1.) How is the legal awareness of the community in the use of yard land based on Kupang City Regional Regulation Number 7 of 2000 concerning RTH? (2.) What are the factors that hinder the legal awareness of the community in the use of yard la? This research is a type of empirical legal research. The results of the study show that the level of legal awareness of the community in the Maulafa sub-district is measured using four indicators of legal awareness according to Soerjono Soekanto, namely legal knowledge, legal understanding, legal attitudes and legal behavior so that it can be concluded that the legal awareness of the community is still relatively low. Educational factors and economic factors are obstacles to the legal awareness of the community in the Oepura Sub-district.